2017
DOI: 10.1016/j.str.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Type-1 Secretion System ABC Transporter

Abstract: Type-1 secretion systems (T1SSs) represent a widespread mode of protein secretion across the cell envelope in Gram-negative bacteria. The T1SS is composed of an inner-membrane ABC transporter, a periplasmic membrane-fusion protein, and an outer-membrane porin. These three components assemble into a complex spanning both membranes and providing a conduit for the translocation of unfolded polypeptides. We show that ATP hydrolysis and assembly of the entire T1SS complex is necessary for protein secretion. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 45 publications
3
53
0
Order By: Relevance
“…The TMD is occluded to either side of the membrane in the presence or absence of nucleotides that was also supported by Pulsed Electron-Electron Double Resonance (PELDOR) measurements in bicelles (Bountra et al, 2017). Occluded conformations have also been reported for other ABC transporters (Lin et al, 2015;Perez et al, 2015;Morgan et al, 2017). We have biochemically shown that McjD adopts a transient outward-open conformation that it is probably not long-lived or well populated to be trapped by PELDOR (Bountra et al, 2017).…”
Section: Introductionsupporting
confidence: 66%
“…The TMD is occluded to either side of the membrane in the presence or absence of nucleotides that was also supported by Pulsed Electron-Electron Double Resonance (PELDOR) measurements in bicelles (Bountra et al, 2017). Occluded conformations have also been reported for other ABC transporters (Lin et al, 2015;Perez et al, 2015;Morgan et al, 2017). We have biochemically shown that McjD adopts a transient outward-open conformation that it is probably not long-lived or well populated to be trapped by PELDOR (Bountra et al, 2017).…”
Section: Introductionsupporting
confidence: 66%
“…9, C and D, yellow circles). In addition, on the kinked helix on the substrate entry window, there is a positively-charged residue that sticks out toward the pore of the window and blocks the window in ADP-bound state of TliD (34). The ConSurf results also verified that this residue was charge-conserved, as all of the 50 homologs had either arginine or lysine at this residue (Fig.…”
Section: Protein Isoelectric Point and Abc Transporter Secretionmentioning
confidence: 72%
“…In this state, PrtD binds the other components PrtE and PrtF [77,[110][111][112]. The full assembly is suggested to reactivate PrtD's ATPase activity and therewith to enable the substrate transport [77,113,114]. A potentially related stimulation by the MFP has previously been demonstrated for the interaction of MacA with MacB [61].…”
Section: Macb and Type I Secretion System Abc Transportersmentioning
confidence: 99%
“…The recently solved structures of the inner membrane ABC transporter component of a type I secretion system (Aquifex aeolicus AaPrtD, part of AaPrtDEF assembly) [77] and that of the ABC transporter MacB from the tripartite multi-drug efflux assembly MacAB-TolC [33,[37][38][39]] invite a structural comparison of these two systems. Both structures are depicted in Fig.…”
Section: Macb and Type I Secretion System Abc Transportersmentioning
confidence: 99%
See 1 more Smart Citation